2014
DOI: 10.1186/s12941-014-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbapenem-resistant Pseudomonas aeruginosa clinical isolates, carrying multiple genes coding for this antibiotic resistance

Abstract: BackgroundCarbapenemase genes are one of the most frequent mechanisms reported in carbapenem-resistant P. aeruginosa; however, description of P. aeruginosa co-harbouring two or more carbapenemases is unusual.MethodsIn this study we evaluated the presence of carbapenemase genes and the clonality of P. aeruginosa isolates obtained from a hospital over a 12-year period. A total of 127 isolates of carbapenem-resistant P. aeruginosa recovered from 109 patients feces (four samples), rectal swab (three samples), nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 20 publications
2
34
0
6
Order By: Relevance
“…Also, we detected P. aeruginosa isolates with more than one carbapenemase gene, of which four of them possessed three genes; blaNDM-1, blaVIM-1 and blaVIM-2. Few studies have reported the coexistence of carbapenemases encoding genes in the same P. aeruginosa isolate such as KPC and IMP-8 in Puerto Rico [37], KPC and VIM in Colombia [38] and SPM-1, KPC-2 and VIM-2 in Brazil [39].…”
Section: Discussionmentioning
confidence: 99%
“…Also, we detected P. aeruginosa isolates with more than one carbapenemase gene, of which four of them possessed three genes; blaNDM-1, blaVIM-1 and blaVIM-2. Few studies have reported the coexistence of carbapenemases encoding genes in the same P. aeruginosa isolate such as KPC and IMP-8 in Puerto Rico [37], KPC and VIM in Colombia [38] and SPM-1, KPC-2 and VIM-2 in Brazil [39].…”
Section: Discussionmentioning
confidence: 99%
“…First reported in Colombia in 2006 (4), subsequent worldwide reports described plasmid and chromosomal genetic contexts for this gene. In Brazil, KPC-producing P. aeruginosa was first described in 2012 (5), followed by a second report (6) that highlighted a worrying increase in KPC-producing P. aeruginosa. However, the genetic context of bla KPC in the Brazilian strains remained unknown.…”
mentioning
confidence: 99%
“…The predominant carbapenemases include New Delhi metallo-β-lactamases (NDM), Oxacillinases (OXA), Verona integron-encoded metallo-β-lactamase (VIM), Imipenemase (IMP), and KPC, which are encoded by the genes bla NDM , bla OXA , bla VIM , bla IMP , and bla KPC , respectively (Nordman, Naas, Poirel, 2011). In Brazil, some types of carbapenemases have been detected more frequently, such as São Paulo metallo-β-lactamase (SPM) in P. aeruginosa isolates (Rossi, 2011;Rizek et al, 2014. ), OXA-23 in Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%